Molecular Cloning of a Functional Fads2 Promoter from Zebrafish - Chung, Hung Hui; Azham, Zulkharnain (Hibiscus Publisher, 2016)
The FADS2 catalyzes the first rate-limiting step in the long chain-polyunsaturated fatty acids (LC-PUFAs) biosynthesis pathway by converting -linolenic acid and linoleic acid into stearidonic acid and -linolenic acid via the -3 and -6 pathways respectively. In mammals, PPAR and SREBP-1c have been implicated in the polyunsaturated fatty acids (PUFAs) mediated transcriptional activation of FADS2 promoter. However, in zebrafish, not much is known regarding the regulation of fads2 transcriptional regulation. Here, in this study, five vectors containing different promoter regions were constructed in order to analyse putative promoter activities. Through truncation analysis, it was found that the 1.2 kb promoter was able to drive luciferase activity to an approximate 40-fold in HepG2 cells. Upon mutagenesis analysis, three sites which are the putative NF-Y, SREBP and PPAR binding sites were found to be essential in driving the promoter activity. Lastly, the 1.2 kb fads2 promoter was able to direct EGFP expression specifically to the yolk syncytial layer (YSL) when transiently expressed in microinjected zebrafish embryos.